A systematic review upon the online content provided for self-management of diabetes (UCC Student Medical Journal, 2024)
Background: Diabetes is a major illness that requires appropriate education in order to increase one's understanding of self-management. With the advancement of the internet, the proliferation of online health-related content in supporting the management of chronic illness like diabetes has been ongoing; however, little is understood on the sort of acceptable and/or effective information attainable online. Objective: The aim of this review is to evaluate the current literature in hindsight of online management in diabetes whilst establishing the effectiveness of online management tools, the quality of the online information, and the methods of obtaining online information. Methods: A series of systematic searches of online databases were conducted in accordance with strictly defined inclusion and exclusion criteria relevant to the research question. Additionally, an evidence-based literature (EBL) checklist tool was used to assess the methodological and reporting quality of each study. Each article was peer-reviewed and screened for any biases. Results: A result of 11 electronic searches were critically appraised using the EBL appraisal checklist tool and all were found to have overall validity. The results indicate an increase use of online technology to empower an understanding of one's own health. Web-based tools like social media were useful in promoting the management of diabetes but were not able to provide quality information. Conclusion: Current research indicates the need for more investigation and future development of readily accessible and qualitative information in order to support the self-management of diabetes.
Keywords: diabetes; diabetic management; self-management; online content